Pemanfaatan Teknologi Digital dan Inovasi Manajemen untuk UMKM Berdaya Saing - Muzakar Isa; Praswati, Aflit Nuryulia; Muhammad Randhy Kurniawan; Ahmada Auliya Rahman; Rafiq Arkana Putra (Universitas Muhammadiyah Surakarta, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in fostering local economic growth. However, many MSMEs struggle with challenges in innovation management and digital marketing, which hinder their competitiveness. This community service initiative was designed to strengthen MSME capacity by offering training in business innovation, digital marketing strategies, and visual content creation for product promotion. The training program aimed to equip participants with the necessary skills to enhance business management, leverage digital platforms for marketing, and create compelling promotional content. The implementation process involved practical training sessions and continuous mentoring to ensure the effective application of the knowledge gained. The results demonstrated that MSME partners successfully adopted the strategies taught, leading to greater product visibility and increased competitiveness in the local market. The practical skills acquired through this program are expected to support long-term business sustainability and foster the growth of participating MSMEs.